PENGEMBANGAN PROGRAM PENDIDIKAN PENCEGAHAN HIV DAN AIDS DI SMAN "X" KOTA SUKABUMI JAWA BARAT - Dante Rigmalia, - (2007)
The Title of this research is Educational Development Program of HIV and AIDS Prevention. The research is based on the writer's thoughts and understanding about the strategic roles of education which will able to reach many people include teenagers. Through education, they will understand the ways to prevent themselves from being infected by HIV and AIDS. Through education students' knowledge and understanding about HIV and AIDS are built, which in return will minimize the stigma and discrimination of the people where living HIV and AIDS accordingly, even more, it will be able to totally eliminate the stigma and discrimination. Having such understanding will create a community where is more discrimination and isolation for the people living with HIV and AIDS, but an opportunity extended by community for people living with HIV and AIDS to access all human rights including education. For this research the writer used the qualitative and quantitative analysis with the subject of research are Headmaster, Teachers, Students, and School Committee. Method used for collecting data was questionnaire, interview, and document analysis. The research also completes the methods by held a workshop activity featured five key note speakers. The Purpose of this research is to figure out of following aspects: people understanding about HIV and AIDS, people attitude toward HIV and AIDS, improvement of educational program concerning HIV and AIDS prevention. Before the workshop, the data showed: 80% understand, 20%more understand, 20% neutral response, 80%positive response attitude and point of view. After the workshop data showed 5%understand, 95 %more understand 100 %positive response, attitude and point of view. The qualitative data analysis results combine with the interview result, to get real subject understanding and attitude. One of the results is that the workshop extend a recommendation to integrate the educational program of HIV and AIDS with school' intra curricular organization such as OSIS, PMR (Youth Red Cross), Pramuka and KPA. In order to support this integrated educational program it is almost important to ensure the human right development (quality), sufficiency/availability of studying facilities, proper network and involvement of all concerned parties. The experts stated based on the workshop result that the integration of educational program of HIV and AIDS prevention to those said school intra and extra curricular is absolutely fit with the objectives of HIV and AIDS education. Thus, this integrated educational program is highly recommended to be extended to Senior High School students.